Visualisasi Hasil Pemeriksaan Laboratorium Pasien Studi Kasus: Parahita Diagnostic Center - Yonathan Ardy C; Halim Budi S. (Jurnal Informatika dan Sistem Informasi, 2015)
Medical Check Up is the important part to control people’s health. By checking up the health in laboratory can help to know someone’s health level. But, sometimes it is too difficult to read the result because the patient does not know the meaning for every items in the result. It means that patient can not conclude the result whether it is good or bad. Another problem faced by patient is the progress for the health level. Sometimes, patients do not have access to the earlier check up result. Visualization is a step to give a illustration to the people about specific description or exposure. Medical and Laboratorium Data Visualization is one step ahead to give the description about patients health level and condition. Thus, the the result can be delivered well. In this research, visualization method will be implemented to the laboratory result, especially for the numeric result. This study make the system which can visualize the patient laboratory result. Patients are also able to know and search the earlier result. The laboratory result is presented in graphical presentation in order to give the patients some description about health level. The system are able to ease the patient know their health condition.